Current concepts about periodontal disease and relationship with systemic diseases - Guimarães, Gustav; Azuma, Mariane M. [UNESP]; Guimarães, Maria R.F.S.G.; Dezan Junior, Eloi [UNESP]; Cintra, Luciano Tavares Angelo [UNESP] (My University, 2016)
Periodontal disease may be characterized by clinical symptoms such as gingival bleeding, tooth mobility, pathologic migration of supportive tissues, and loss of chewing ability. In addition, it may be classified as an inflammatory disorder of the supporting tissue of the tooth, which has different etiologies and different degrees of severity. In this chapter, we discuss the main manifestations of gingivitis, chronic periodontitis, aggressive periodontitis, and periodontal disease resulting from systemic diseases. In addition, we discuss the treatment options, highlighting the conventional periodontal therapy, systemic administration of antibiotics, and surgical treatments.
Keywords: Aggressive periodontitis; Chronic periodontitis; Gingivitis; Periodontal medicine